Youth, Da'wah and Tik Tok: A Case Study of Husain Basyaiban - Jumiyati; Pipir Romadi; Riski Alwi,S.Sy.,MH; satria, Budi satria (Rumah Jurnal, 2023)
This paper shows TikTok as a medium of da’wah among young people. The large number of social media users today is a solution and a way for preachers as targets for their da’wa. The author used interviews, observations, documentation, descriptive and ethnographic work through Husain Basyaiban TikTok account. The findings of this study demonstrate that the preachers use social media users as targets for their da’wah. One of the media that is widely used is TikTok application. The various videos on TikTok are from positive and negative things, everything returns to how we use the application. Therefore, there are also many young preachers who are actively preaching on TikTok, one of them is Husain Basyaiban. His appearance on TikTok has attracted a lot of attention in various circles, especially among young people. Husain's da'wah was effective because it was based on the Qur'an and Hadis, which has a beneficial effect. Additionally, the way he delivered his message was excellent, including the language he used, his ethics, his public speaking abilities, and his eye-catching fashion sense. This is also a motivation for other young people to participate in preaching to convey Islamic sharia and spread Islam in various countries simply by using social media, namely TikTok, rather than traveling there in person.